Pelatihan Digitalisasi Usaha Menggunakan Media Sosial Untuk Pemasaran - Susilo, Arif; Arwan Sulaeman, Asep; Setyawan, Wisnu; Rohim, Abdul (VINICHO MEDIA PUBLISINDO, 2024)
Business digitalization training using social media for marketing is very important in the context of the current digital era. Social media has become the primary platform for many businesses to promote their products and services, as well as to interact directly with customers. However, many small and medium business (SME) owners may not fully understand the full potential and effective strategies for optimally utilizing social media. This training aims to investigate effective training approaches to help PT. Gecok Halal Indonesia understands and implements digitalization strategies using social media. Recommended training methods include practical learning about various social media platforms such as Facebook, Instagram, and LinkedIn, as well as digital marketing techniques such as SEO (Search Engine Optimization), the use of paid advertising, and campaign performance analysis. It is hoped that the results of this service will provide practical guidance for trainers and consultants who wish to support SMEs in increasing their online presence through social media. With increasing digital competence, it is hoped that SMEs can be more competitive in this increasingly connected global market.